A life of misery : a psychosocial perspective on Annie Wilkes from Stephen King’s Misery. - Aliaga Bazaes, José Ignacio (Universidad de Santiago de Chile, 2019)
Integrantes: José Ignacio Aliaga Bazaes, Valery Verónica Díaz Guerrero, Fernanda Giselle Fernández Cofré, María Cristina Veas Caro
Keywords: King, Stephen, 1947- . Misery; Arquetipo (psicología) en literatura; Psicología de la literatura